Cortisol, salivary alpha-amylase and children's perceptions of their social networks. (3rd March 2016) - Ponzi, Davide; Muehlenbein, Michael P.; Geary, David C.; Flinn, Mark V.
Abstract : In recent years there has been a growing interest in the use of social network analysis in biobehavioral research. Despite the well-established importance of social relationships in influencing human behavior and health, little is known about how children's perception of their immediate social relationships correlates with biological parameters of stress. In this study we explore the association between two measures of children's personal social networks, perceived network size and perceived network density, with two biomarkers of stress, cortisol and salivary alpha-amylase. Forty children (mean age = 8.30, min age = 5, and max age = 12) were interviewed to collect information about their friendships and three samples of saliva were collected. Our results show that children characterized by a lower pre-interview cortisol concentration and a lower salivary alpha-amylase reactivity to the interview reported the highest density of friendships. We discuss this result in light of the multisystem approach to the study of children's behavioral outcomes, emphasizing that future work of this kind is needed in order to understand the cognitive and biological mechanisms underlying children's and adolescents' social perceptual biases.